Plant anticancer agents, l. cytotoxic triterpenes from sandoricum koetjape stems - Norito Kaneda (2018)
A new ring-A secotriterpene, koetjapic acid [1], and five known compounds, 3-oxo-olean-12-en-29-oic acid [2] (a novel natural product), katonic acid [3], (−)-alloaromadendrene, (−)-caryophyllene oxide, and (+)-spathulenol, have been isolated and characterized from a cytotoxic Et2O-soluble extract of Sandoricum koetjape stems. Of these compounds, 2 and 3 demonstrated significant cytotoxic activity against cultured P-388 cells (ED50values of 0.61 and 0.11 μg/ml, respectively). Significant, albeit less intense, cytotoxicity was also observed with a variety of cultured human cancer cells. The13C-nmr chemical shifts of these triterpenes were assigned unambiguously using selective INEPT nmr experiments. Aside from compounds 2 and 3, these substances were not toxic with cultured cells. © 1992, American Chemical Society. All rights reserved.